Gencsy Béla egyházvezetői tevékenységének főbb irányvonalai az államszocializmus idején - Szamborovszkyné Nagy Ibolya; Самборовскі-Нодь Ібоя; Ibolya Szamborovszky-Nagy (KRE HTK Egyháztörténeti Kutatóintézet, 2023)
Gencsy Béla harminc évig állt a Kárpátaljai Református Egyház (továbbiakban KRE) élén, s immár négy évtizede annak, hogy elhunyt (1982), ám sem egyházvezetői, sem lelkészi tevékenysége, akárcsak életútja mind a mai napig nincs feltárva.1 A kutatás alapvető célja, hogy ismertessük Gencsy Béla tevékenységének főbb irányvonalait, melyekről előbb esperesi, majd dékáni (főpresbiteri), végül püspöki működése során a fennmaradt korabeli dokumentumok adnak képet. Emellett arra törekedtünk, hogy – túllépve a róla kialakított egysíkú jellemzésen – láttassuk az adott korszak és tér meghatározta lehetőségek ellentmondásos mechanizmusait, melyek nemcsak az egyházvezető, de a kárpátaljai református egyházközségek tevékenységét is determinálták. Jelen tanulmányban az egykori püspök egyházvezetői aktivitásának főbb vonásait és állomásait mutatjuk be 1949 és 1978 között. Nem tűztük ki azonban célként sem Gencsy Béla teljes életútjának, sem lelkészi tevékenységének teljes körű bemutatását, mivel annak keretei túlmutatnak egy kutatási tanulmány terjedelmén.

Abstract. Béla Gencsy was the head of the Transcarpathian Reformed Church for thirty years. Although four decades have passed since his death (1982), neither his activity as a church leader and as a minister, nor his life has been revealed up to now. This fact encouraged the author to investigate the main directions of Béla Gencsy’s activity as a church leader, based on the contemporary documents of his activity as a moderator, then as a dean and finally as a bishop. In addition, the author sought to go beyond the one-sided characterization made of him as a church leader and to show the contradictory mechanisms of the possibilities defined by the given era and space, that determined not only the church leader’s activity, but also that of the Reformed parishes in Transcarpathia. The present study covers the period between 1949 and 1978. Because of the current state of research and the criteria set out, a primary source study was carried out based mostly on archival documents. The surviving contemporary documents revealed an ambivalent trajectory emerging from Béla Gencsy’s activity as a church leader. On the one hand, it is clear that he always and in any case wanted to observe and enforce the Soviet religious laws. On the other hand, his actions and reactions were steps taken in a give-and-take system, in return for which the bishop was granted the opportunity to raise and/or solve issues that had not been addressed before.
The Main Directions of Béla Gencsy’s Activity as a Church Leader during the State Socialism
Szerkesztők és tartalom: https://htk.kre.hu/index.php/hagyomany-identitas-tortenelem-2022.html
Teljes kiadvány: https://htk.kre.hu/images/doc/kiadvanyok/reformacio-oroksege/HIT-2022/HIT2022_full.pdf
Keywords: Gencsy Béla; Kárpátaljai Református Egyház; Kárpátalja